Answer:
36.5
Step-by-step explanation:
5(1+6.3)
To find the other endpoint with a given endpoint and midpoint, you subtract the midpoint values from the endpoint, then with whatever the answer is, you subtract that from the midpoint.
Answer:
First, we bring the equation to the form ax²+bx+c=0, where a, b, and c are coefficients. Then, we plug these coefficients in the formula: (-b±√(b²-4ac))/(2a) . See examples of using the formula to solve a variety of equations.
4x + 5y = 9
5y = -4x + 9
y = -4/5x + 9/5......slope intercept form (y = mx + b)
In y = mx + b form, which is what this equation is in now, the slope is in the m position and the y int is in the b position
y = mx + b
y = -4/5x + 9/5
so ur slope(m) = -4/5 and ur y int (b) = 9/5